PEMODELAN MOTIF KERAMIK DENGAN TEKNIK PENGGABUNGAN BANGUN-BANGUN GEOMETRI DATAR DENGAN KONSEP TRANSFORMASI - Dzurotul Mutimmah; Puput Bahtiar Rifa'i (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
The objectives of this research are to obtain the procedure of ceramic motif design with through merging some objects flat geometry by concept of transformation. The research method covered the ceramic motif design with axis symmetry pattern and central symmetry pattern, which are constructed from triangle and circle. Finally, we simulate the design of ceramic motif by using computer software Maple 12.